2021
DOI: 10.1155/2021/8868940
|View full text |Cite
|
Sign up to set email alerts
|

Response of Bread Wheat (Triticum aestivum L.) to Potassium (K) and Blended NPS Fertilizer Rates in the Nitisols of Southern Ethiopia

Abstract: Wheat is the most important cereal crop ranking 4th in total grain production and area coverage in Ethiopia. However, its productivity is low compared to the yield obtained under the research station. Multinutrient deficiency, low/no chemical fertilizer usage, and poor management practices are among the major constraints. Thus, response of bread wheat to NPS and K fertilizer rates was evaluated in the nitisols at Kokate, Wolaita Sodo, Southern Ethiopia, in 2016. Four rates of KCl (0-0-60) (0, 25, 50, and 75 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 30 publications
(36 reference statements)
5
8
0
Order By: Relevance
“…In agreement with the present study, Desta & Almayehu (2020) reported the highest (50.07) NKS under combined application of 150/92 kg NPSB/N ha −1 fertilizer rates. Increasing NKS was also reported by Malghani et al (2010) and Tesfaye, Laekemariam & Habte (2021) due to the increasing rate of NPKS fertilizer. Debnath et al (2011) and Muhammad et al (2009) also reported that Boron application significantly affected wheat’s NKS.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…In agreement with the present study, Desta & Almayehu (2020) reported the highest (50.07) NKS under combined application of 150/92 kg NPSB/N ha −1 fertilizer rates. Increasing NKS was also reported by Malghani et al (2010) and Tesfaye, Laekemariam & Habte (2021) due to the increasing rate of NPKS fertilizer. Debnath et al (2011) and Muhammad et al (2009) also reported that Boron application significantly affected wheat’s NKS.…”
Section: Resultssupporting
confidence: 75%
“…Other research findings also indicated that the application of NPK fertilizers had a potential role in the number of TT and PT production of wheat ( Abera, Tana & Dessalegn, 2020 ; Baque et al, 2006 ; Getachew & Dechassa, 2014 ; Malghani et al, 2010 ) due to their positive role in stimulating vegetative growth and development. In southern Ethiopia, the higher number of TT and PT from the combined effect of NPS and KCl was reported than the unfertilized plots ( Tesfaye, Laekemariam & Habte, 2021 ). Similarly, the highest number of TT (421 tillers m −2 ) and PT (375.7 tillers m −2 ) were reported with the application of NPSB supplied with N in central highland Ethiopia ( Desta & Almayehu, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations